STRATEGI KOALISI RIAU BERSATU DALAM PEMENANGAN PASANGAN CALON GUBERNUR & WAKIL GUBERNUR SYAMSUAR-EDY NATAR NASUTION PADA PILKADA PROVINSI RIAU TAHUN 2018 - Gilman Ilhafa Arisma; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The 2018 Riau Provincial Pilkada is part of the implementation of the Pilkada Simultaneously in Indonesia which was held on June 27, 2018. In the 2018 Riau Provincial Election, four pairs of candidates for Governor & Deputy Governor participated. The candidate pair for Governor & Deputy Governor of Riau Province number 1 Syamsuar-Edy Natar Nasution was carried by the United Riau Coalition consisting of a combination of the PAN Party, the Prosperous Justice Party (PKS) and the Nasdem Party. In the 2018 Riau Provincial Pilkada, the Syamsuar-Edy Natar Nasution pair succeeded in winning over the other candidate pairs by obtaining a total number of votes of 799,289 votes (38.2%) then followed by candidate 4 Arsyadjuliandi Rahman-Suyatno with 507,187 votes (24.2%), then candidate pair number 3 Firdaus-Rusli Effendi with total votes of 416,248 votes (19.9%), and the last candidate pair number 2 Lukman Edy-Hardianto with 369,802 votes (17.7%) .               In this study, using a qualitative descriptive method with informants from the United Riau Coalition team, which was the winning team of the Syamsuar-Edy Natar Nasution pair in the 2018 Riau Provincial Election with data collection techniques through interviews and from documentation during the Pilkada implementation.The research results in this study indicate that the Riau United Coalition applies a Mobilizing Strategy and a Chasing Strategy. The mobilizing strategy was carried out to mobilize supporters of political parties and first-time voters, meanwhile, the strategy of chasing was carried out by conducting dialogical campaign activities at 356 points, door-to-door activities, approaching community leaders and by utilizing media campaigns. As for the obstacle is the spread of hoax news and a very long campaign period, making the campaign costs of the candidate pairs high. Keywords: Strategy, Coalition, Mobilizing, Chasing.